Determination of Polyphenol Content in Sawo Fruit (Manilkara zapota) Based on Geographical Location - Harni Sartika Kamaruddin; Angriani Angriani; Carla Wulandari Sabandar (Journal of Tropical Pharmacy and Chemistry, 2021)
Background: Sawo fruit (Manilkara zapota (L.) P.Royen) is rich in antioxidant compounds like polyphenols, and has long been used to treat diarrhea and thypoid by natives of Toari and Langori villages of Kolaka district of Southeast Sulawesi Province. Both villages located at different geographical location according to their altitudes from the sea level. The polyphenols content of sawo fruit from these villages that has a correlation with its antioxidant activity has yet investigated and thus need more research. Objective: This study was aimed to determine the content of polyphenols in sawo fruit based on geographical growth difference, that are Toari and Langori villages. Material and Methods: The fruits were collected from two locations of the Kolaka district that are Langori and Toari villages. The polyphenols content in the methanol extract of Sawo fruit was determined qualitatively using FeCl3 and quantitatively using the Folin-Ciocalteu reagent measured by UV-Visible spectrophotometry. Gallic acid was used as the standard polyphenol of the assay. Results: The polyphenols content of sawo fruit from Langori found to be 1.48113 mg/g, while fruits from Toari contained 1.55747 mg/g of polyphenolics. Conclusion: The study showed that there was an influence of the geographical growth on the content of polyphenolics of sawo fruits.